2016
DOI: 10.5964/jnc.v2i2.17
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between problem size and fixation patterns during addition, subtraction, multiplication, and division

Abstract: Eye-tracking methods have only rarely been used to examine the online cognitive processing that occurs during mental arithmetic on simple arithmetic problems, that is, addition and multiplication problems with single-digit operands (e.g., operands 2 through 9; 2 + 3, 6 x 8) and the inverse subtraction and division problems (e.g., 5 -3; 48 ÷ 6). Participants (N = 109) solved arithmetic problems from one of the four operations while their eye movements were recorded. We found three unique fixation patterns. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…The current issue completes the first full year of publication and accomplishes its target of three issues for the year, accompanying the initial issue that appeared near the end of 2015. I am particularly pleased that the Journal has been able to publish a range of articles that start to represent at least some of the diversity of work in numerical cognition, including for example developmental questions tested at age 4 and beyond (Knudsen, Fischer, Henning, & Aschersleben, 2015;Starr & Brannon, 2015), cross cultural issues (Morrissey, Liu, Kang, Hallett, & Wang, 2016), analysis of the trajectory of real world mathematics skills (Sullivan, Frank, & Barner, 2016) and the cognition that supports different arithmetic processes (Curtis, Huebner, & LeFevre, 2016). In addition, the Journal has addressed and discussed conceptual issues in the research priorities for the field (see Alcock et al, 2016, and accompanying commentaries).…”
mentioning
confidence: 99%
“…The current issue completes the first full year of publication and accomplishes its target of three issues for the year, accompanying the initial issue that appeared near the end of 2015. I am particularly pleased that the Journal has been able to publish a range of articles that start to represent at least some of the diversity of work in numerical cognition, including for example developmental questions tested at age 4 and beyond (Knudsen, Fischer, Henning, & Aschersleben, 2015;Starr & Brannon, 2015), cross cultural issues (Morrissey, Liu, Kang, Hallett, & Wang, 2016), analysis of the trajectory of real world mathematics skills (Sullivan, Frank, & Barner, 2016) and the cognition that supports different arithmetic processes (Curtis, Huebner, & LeFevre, 2016). In addition, the Journal has addressed and discussed conceptual issues in the research priorities for the field (see Alcock et al, 2016, and accompanying commentaries).…”
mentioning
confidence: 99%
“…Research on procedure selection has consistently demonstrated that participants report greater use of non-retrieval procedures on division and subtraction than on addition and multiplication, especially for large problems (Campbell & Xue, 2001;Robinson et al, 2002). In accord with this finding, gaze duration and fixation count patterns appear to deviate substantially as problem size increases for division and subtraction problems (Curtis et al, 2014). Thus, the goal of this thesis was to assess how eye movement patterns are affected when adults of various skill levels (i.e., participants who primarily use memory retrieval vs. participants who readily use non-retrieval procedures) solve simple division problems.…”
Section: The Present Researchmentioning
confidence: 76%
“…Experiment 1A (i.e., the Self-Report condition) was designed to address two primary goals. First, I wanted to replicate patterns of performance for division that were reported by Curtis et al (2014). Replicating these findings would support the claim that overall performance is not drastically affected when participants provide self-reports.…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations